Single-cell transcriptome atlas of lamprey exploring Natterin- induced white adipose tissue browning - Yue Pang; Yating Qin; Zeyu Du; Qun Liu; Jin Zhang; Kai Han; Jiali Lu; Zengbao Yuan; Jun Li; Shanshan Pan; Xinrui Dong; Mengyang Xu; et al. (Nature Communications)
Abstract Lampreys are early jawless vertebrates that are the key to understanding the evolution of vertebrates. However, the lack of cytomic studies on multiple lamprey organs has hindered progress in this field. Therefore, the present study constructed a comprehensive cell atlas comprising 604,460 cells/nuclei and 70 cell types from 14 lamprey tissue samples. Comparison of cellular evolution across species revealed that most lamprey cell types are homologous to those in jawed vertebrates. We discovered acinar- and islet-like cell populations despite the lack of parenchymal organs in lampreys, providing evidence of pancreatic function in vertebrates. Furthermore, we investigated the heterogeneity of lamprey immune cell populations. Natterin was highly expressed in granulocytes, and NATTERIN was localized to the lipid droplets. Moreover, we developed a transgenic mouse model expressing Natterin to elucidate the role of NATTERIN in lipid metabolism, whereas the browning of white adipose tissue was induced. These findings elucidate vertebrate cellular evolution and advance our understanding of adipose tissue plasticity and metabolic regulation in lampreys.